Creating killer interactive web sites : the art of integrating, interactivity and design - 4 0 16; Sather, Andrew; 5 (Indianapolis : Hayden Books, 1997)
Reveals the secrets and strategies of Adjacency, the Web design firm responsible for many successful consumer brand sites on the Internet, including Land Rover, Rollerblade, and PowerBar; featuring photographs, examples, and case studies, and discussing the use of various design programs, graphics, animations, and other tools.
Cover title.;Includes index.
Adult;Adult
Keywords: 2 -- 0; 6; Design.;Design. -- Web sites;Web sites; 20; 2